Elaboration of bio-epoxy/benzoxazine interpenetrating polymer networks: a composition-to-morphology mapping. Issue 4 (4th January 2018) - Puchot, L.; Verge, P.; Peralta, S.; Habibi, Y.; Vancaeyzeele, C.; Vidal, F.
Abstract : Real interpenetrating polymer networks obtained from the sequential polymerization of epoxy and benzoxazine networks, with highly improved mechanical properties. Abstract : An interpenetrating polymer network (IPN) refers to a type of polymer blend in which two chemically distinct networks coexist, benefiting from the assets of each of them. When polybenzoxazine and epoxy are concerned, the elaboration of IPN faces competitive reactions and remains challenging. Hereby, the feasibility of the elaboration of IPNs between a diglycidyl ether of cardanol (poly(CDGE)) and polybenzoxazine (poly(EDBz)) is demonstrated. Isophorone diamine was selected as a hardener, as it is exclusively involved in the epoxy network formation in the studied temperature range. Materials with various ratios of CDGE/EDBz were prepared under a suitable sequential curing process, promoting first the cross-linking of the epoxy polymer before the growth of the polybenzoxazine network. DMA and AFM characterization highlighted clear interpenetrated polymeric structures based on poly(CDGE)/poly(EDBz) materials with different morphologies depending on the composition of the material, yet with enriched phases of polybenzoxazine within the epoxy network. A tremendous enhancement of the mechanical properties of the material as a function of the polybenzoxazine content was observed. Interestingly, the materials composed of 20 wt% to 40 wt% of polybenzoxazine exhibit a single mechanical relaxation temperature demonstrating an efficient polymer chain interpenetration having enriched domains below 50 nm.